2001
DOI: 10.1039/b109637k
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The radical addition of various xanthates to allyl or vinyl boronates occurs smoothly in the presence of a small amount of lauroyl peroxide as initiator to give good yields of usefully functionalised boronates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 13 publications
(5 reference statements)
0
24
0
Order By: Relevance
“…This constraint is seldom obeyed in the case of additions to vinyl pinacolato boronate 14 as the corresponding adduct radical 15 is stabilized by delocalization into the empty orbital on the boron atom, and this radical is in many cases more stable than initial radical 8 . Indeed, additions to vinylBpin ( 14 ) are capricious and often low‐yielding . In contrast, radicals 17 from addition to vinylB(MIDA) ( 16 ) cannot benefit from such stabilization and are in general less stable than initial radical 8 .…”
Section: Resultsmentioning
confidence: 99%
“…This constraint is seldom obeyed in the case of additions to vinyl pinacolato boronate 14 as the corresponding adduct radical 15 is stabilized by delocalization into the empty orbital on the boron atom, and this radical is in many cases more stable than initial radical 8 . Indeed, additions to vinylBpin ( 14 ) are capricious and often low‐yielding . In contrast, radicals 17 from addition to vinylB(MIDA) ( 16 ) cannot benefit from such stabilization and are in general less stable than initial radical 8 .…”
Section: Resultsmentioning
confidence: 99%
“…The Zard group recognized this challenge and addressed it by tuning the boron ligand set (Scheme ) . In two previous reports, the authors found that the radical addition reaction of xanthates and alkenylB(pin) reagents was inefficient relative to the reaction with other alkenes . The authors attributed the poor overall reactivity to the intermediacy of stabilized radical 3 (L 2 = pin).…”
Section: Introductionmentioning
confidence: 99%
“…Strong polar effects favor an efficient and selective iodine-atom transfer over oligomerization. [43][44][45] a-Haloboronic esters have been used in tin-mediated (Scheme 1A) [46][47][48][49] and metal-catalyzed radical processes. Based on these simple considerations,itisexpected that iodine-atom transfer between 1-iodoalkylboronic esters and alkenes should be possible,b ut still challenging,d ue to moderate thermodynamic and polar effects.…”
mentioning
confidence: 99%
“…[50][51][52] Chen and co-workers have reported Pd 0 -catalyzed cyclopropanation of norbornene using potassium iodomethyltrifluoroborate. [43,44,46,[57][58][59][60][61] and to ate complexes of vinylboronates. Radical stabilization energies (RSEs) of 1-borylated radicals and resonanceh ybrids of boronic esters derived radicals.…”
mentioning
confidence: 99%
See 1 more Smart Citation